2018
DOI: 10.1016/j.tjem.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off points for screening at-risk drinking by AUDIT-C Korean version at emergency department

Abstract: PurposeTo reduce problems caused by alcohol drinking, it is necessary to identify those with ‘at-risk drinking’ behavior to maximize therapeutic access or intervention. To this end, we sought to determine the cut-off point for screening of at-risk drinking by the Korean version of the AUDIT-C (Alcohol Use Disorder Identification Test-Consumption).Materials and methodsWe obtained data from the scientific research project of “the supervision of the Korea Center for Disease Control and Prevention (KCDCP)” in 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Neumann et al reported that the screening properties of AUDIT are superior to those of biochemical markers such as %CDT, MCV, and GGT for the detection of alcohol problems among trauma patients, and they are not significantly clinically enhanced by the use of biochemical markers [19]. Other previous studies conducted in primary care and ED settings reported that the AUC of AUDIT-C for detecting any alcohol use disorder was > 0.9 for both men and women, which was comparable with the AUC calculated in our study [19, 27, 42, 43]. Consistent with previous findings, our results confirm that AUDIT-C is a useful and an accurate tool to screen for alcohol problems in various clinical settings, and we suggest that AUDIT-C is a reliable tool to detect alcohol problems among suicide attempters.…”
Section: Discussionsupporting
confidence: 82%
“…Neumann et al reported that the screening properties of AUDIT are superior to those of biochemical markers such as %CDT, MCV, and GGT for the detection of alcohol problems among trauma patients, and they are not significantly clinically enhanced by the use of biochemical markers [19]. Other previous studies conducted in primary care and ED settings reported that the AUC of AUDIT-C for detecting any alcohol use disorder was > 0.9 for both men and women, which was comparable with the AUC calculated in our study [19, 27, 42, 43]. Consistent with previous findings, our results confirm that AUDIT-C is a useful and an accurate tool to screen for alcohol problems in various clinical settings, and we suggest that AUDIT-C is a reliable tool to detect alcohol problems among suicide attempters.…”
Section: Discussionsupporting
confidence: 82%
“…Alcohol Consumption Variables: There are different well-established international screening tools for assessing alcohol use among any given population [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Generally, the drinking construct in alcohol consumption surveys is measured in terms of a combination of frequency and quantity of alcohol consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, higher AUDIT-C scores indicate greater likelihood of problem drinking. A score of 0 reflects no alcohol consumption; 3 or more for women and 4 or more for men is positive; 8 or more is an indication of dependency symptoms and harmful alcohol use [ 29 , 36 ]. Based on this guidance, cutoffs were used to convert AUDIT-C composite scores into four mutually exclusive analysis groups that classify survey participants into four risk categories by their frequency and quantity of alcohol consumption based on standardized drink sizes: (a) 0 as “non-drinkers” at no-risk; (b) 1–4 as “light drinkers” at low-risk; (c) 5–8 as “moderate drinkers” at increased-risk; (d) 9–12 as “heavy and frequent drinkers” at severe-risk [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Section two included questions related to social behaviours including intimate partner violence (IPV); alcohol consumption; and tobacco use. Alcohol consumption was assessed using AUDIT-C. which is an internationally recognized brief alcohol screening tool [38]. The tool assesses alcohol consumption by asking three questions focusing on the frequency and level of alcohol consumption.…”
Section: Data Collection Tool and Measuresmentioning
confidence: 99%